1992
DOI: 10.1139/x92-049
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in nitrate reductase activity in needles of high-elevation red spruce trees

Abstract: To assess seasonal and site variation in foliar nitrate reductase activity and its utility as a biochemical marker for the uptake of nitrogen oxide pollutants in high-elevation forests, we measured nitrate reductase activity in current-year needles of red spruce (Picearubens Sarg.) saplings at two high-elevation stands (1935 and 1720 m) in the Great Smoky Mountains, North Carolina. Measurements spanned two growing seasons between September 1987 and September 1988. Nitrate reductase activity peaked near 60 nmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…We assumed that effective metabolism of nitrogen originating from pollution or excessive N load may be a key factor responsible for these differences. Enhanced sulfate and nitrate from cloud-water deposition was assumed to be a major factor in the high mortality and growth decline of Picea rubens in high-altitude spruce/fir forests of the northeastern U.S.A. (Tjoelker et al, 1992;Adams et al, 1992). These studies suggested that cloudwater N inputs increase frost susceptibility, and that repeated winter injury may play a role in red spruce decline.…”
Section: Introductionmentioning
confidence: 99%
“…We assumed that effective metabolism of nitrogen originating from pollution or excessive N load may be a key factor responsible for these differences. Enhanced sulfate and nitrate from cloud-water deposition was assumed to be a major factor in the high mortality and growth decline of Picea rubens in high-altitude spruce/fir forests of the northeastern U.S.A. (Tjoelker et al, 1992;Adams et al, 1992). These studies suggested that cloudwater N inputs increase frost susceptibility, and that repeated winter injury may play a role in red spruce decline.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrate reductase activity has been measured in many forest tree species, particularly in conifers (Theobald and Smith 1974;Adams and Attiwill 1982;Schmidt et al 1991;Tjoelker et al 1991). Experiments with conifers have provided most of the data concerning N-form utilization of trees, and have generally shown that reduced nitrogen (ammonium) is the preferred N-source (Gijsman 1991;Sarjala 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Although soil NO 3 --N availability is the most frequently cited factor that regulates plant NRA (e.g., Tjoelker et al 1992;Troelstra et al 1995), it seems unlikely that the change in soil NO 3 --N availability functioned as a major regulating factor of leaf NRA in the present study. Soil NO 3 --N availability generally fluctuates temporally, although we lack sufficient information on seasonal changes in soil NO 3 --N availability at the study site.…”
Section: Leaf Nra Controlled By Leaf Growth Stagementioning
confidence: 67%
“…Soil NO 3 --N availability is a frequently cited external cause because NR is substrateinducible. For example, temporal changes in NRA corresponding with changes in soil NO 3 --N availability were observed in shoots of Deschampsia flexuosa (Troelstra et al 1995) and Picea rubens needles (Tjoelker et al 1992). Troelstra et al (1995) observed that the foliar NRA of D. flexuosa was high in early spring and concluded that the foliar NRA of this species might in part be induced by low ambient temperature, in addition to high soil NO 3 --N availability.…”
Section: Introductionmentioning
confidence: 99%